KOMUNIKASI ANTARPRIBADI PASANGAN YANG MENJALANI HUBUNGAN JARAK JAUH (LONG DISTANCE RELATIONSHIP) DI KOTA DENPASAR - Lokasari, Putu Vita; Nugroho, Wahyu Budi; Zuryani, Nazrina (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2019)
ABSTRACT This study aims to determine secondary communication with couples who experience long distance relationships (LDR). The objects are couples who experience LDR which one partner is in the Denpasar city. The theory used in this research is the communication process from a mechanistic perspective by Aubrey Fisher. This process occurs when communicators convey messages verbally, using cues (signs and movements of limbs), and writing so the message can be received by the communicant. The results of this study indicate communication that occurs the LDR couples are very different from couples that not in LDR. Couples who experience LDR are very dependent on communication media as an intermediary in long-distance communication. LDR couples use various methods to keep their relationship good such as give time to their partner to restore emotional states to reconcile in dealing with conflict. Keywords: Long Distance Relationship, Reconcile, Secondary Communication.